2013
DOI: 10.1111/ivb.12033
|View full text |Cite
|
Sign up to set email alerts
|

Tunic cell populations during fusion events in the colonial ascidian Didemnum vexillum (Tunicata)

Abstract: We documented changes in the abundance and distribution patterns of tunic cells involved in the allorecognition response of the colonial aplousobranch Didemnum vexillum, whose zooids do not share a common vascular system. A histological examination of the fusion zone of isogeneic (CIAs) and allogeneic (CAAs) fused colony assays revealed that tunic cuticles were rapidly regenerated. The underlying tunic matrix fused readily in all assays and controls. We identified four different types of tunic cells. Phagocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In common with many other colonial tunicates, adjacent D. vexillum colonies can fuse, at least transiently, to form chimeric colonies ( Smith et al, 2012 ; Rinkevich & Fidler, 2014 ; Sellers, Fagerberg & Litvaitis, 2013 , this study). While in botryllid ascidians, allorecognition between colonies is strongly influenced by highly polymorphic genetic loci ( Rinkevich, 2004 ; Rinkevich, 2011 ; Rinkevich & Weissman, 1992 ; Rinkevich & Weissman, 1987 ; Rinkevich, 1996 ), for D. vexillum itself little is known on genetic mechanisms associated with chimeric colony formation ( Smith et al, 2012 ; Rinkevich & Fidler, 2014 ; Sellers, Fagerberg & Litvaitis, 2013 , this study). Moreover, fusion in botryllid ascidians begins via vascular anastomoses (‘cytomictical chimerism’; sensu ( Rinkevich & Weissman, 1987 )), which enables stem cells circulating throughout the chimeric colony to initiate what is, in effect, ‘cell lineage competition’ between the two genotypes in the chimera.…”
Section: Discussionmentioning
confidence: 65%
“…In common with many other colonial tunicates, adjacent D. vexillum colonies can fuse, at least transiently, to form chimeric colonies ( Smith et al, 2012 ; Rinkevich & Fidler, 2014 ; Sellers, Fagerberg & Litvaitis, 2013 , this study). While in botryllid ascidians, allorecognition between colonies is strongly influenced by highly polymorphic genetic loci ( Rinkevich, 2004 ; Rinkevich, 2011 ; Rinkevich & Weissman, 1992 ; Rinkevich & Weissman, 1987 ; Rinkevich, 1996 ), for D. vexillum itself little is known on genetic mechanisms associated with chimeric colony formation ( Smith et al, 2012 ; Rinkevich & Fidler, 2014 ; Sellers, Fagerberg & Litvaitis, 2013 , this study). Moreover, fusion in botryllid ascidians begins via vascular anastomoses (‘cytomictical chimerism’; sensu ( Rinkevich & Weissman, 1987 )), which enables stem cells circulating throughout the chimeric colony to initiate what is, in effect, ‘cell lineage competition’ between the two genotypes in the chimera.…”
Section: Discussionmentioning
confidence: 65%
“…Hemocytes in the tunic have been identified as effector cells of allorecognition in aplousobranch ascidians (Ishii et al, ; Sellers et al, ) and present a possible mechanism for the genetic changes we observed. Phagocytes and morula cells are abundant at the fusion junction between allogeneic colonies of D. vexillum (Frey, ; Sellers et al, ), with morula cells proposed as effector cells in allorecognition in this species (Sellers et al, ). Long‐term studies that track the movement of these cell types over time throughout fused colonies will be informative in determining the extent to which they are involved in the genotypic changes we saw in chimeric colonies of D. vexillum .…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies on fusion in aplousobranch ascidians have shown that interactions occur between mobile tunic cells at allogeneic contact sites (Dias & Yokoyama, ; Ishii et al, ; Sellers et al, ). Allogeneic zooids in chimeric colonies of D. listerianum may also intermingle, leading to changes in the distribution of genotypes in fused colonies (Bishop & Sommerfeldt, ; Sommerfeldt et al, ), a process that has not yet been investigated in D. vexillum .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations